Aplicación de cuidados en salud a pacientes con discapacidades que pertenecen a la Fundación Voluntad de Dios del cantón La Maná en el periodo primer semestre del 2013 - Campoverde García, Paola del Rocío (2013)
Disability sees the issue mainly as a socially created problem and principally as a matter of integrating people into society where disability is not an attribute of the person, but rather a complex set of conditions, many of which are created and social environment. From this social model we're introduced to the problem of social exclusion of people with disabilities, which are labeled, stigmatized , marked for life by the mere fact of being different and placed in a position of inferiority. This has generated attitudes of rejection , shame , distress , discomfort and over- familiar behavior , leading to treat them as people unable to fend for themselves, enhanced and developed. So then the subjects with disabilities , being theoretically subject to the same rights as others , are prevented from exercising them by discriminatory behavior that society shows them , making them feel like " second class citizens " . In summary and as a final thought, we argue that although there are social factors that have evolved towards greater integration of disabled individuals, there are still a lot of debt in relation to their social integration. As described above raises the following research question: What is the " APPLICATION OF HEALTH CARE IN PATIENTS WITH DISABILITIES THAT BELONG TO GODS FOUNDATION OF CANTON MANA IN THE FIRST HALF OF 2013 PERIOD. "? God's foundation is located in the Canton La Maná , one of the seven districts of the province of Cotopaxi , founded by Carlos Lozada Quintana dealer who installed a hamlet in the late nineteenth century and early twentieth century in the which became commercially available products of the mountains and coast. In the center of Ecuador. A An altitude of 411 meters above sea level , La cantonización occurred on May 19, 1986 . It has a total area of 66,258 hectares. It is the sixth canton in the province of Cotopaxi. The objective of this research is to determine the care that applies to disabilities that lead to the reduction of risk and complications. The specific objectives are framed in: Select psychological support needs , requiring patients with disabilities and family members , as well as classify the knowledge possessed by caregivers to enhance skills for the care of disabled Being the main hypothesis, clearing With proper care provided by caregivers supervised by qualified staff and improve the quality of life of people with disabilities. ? We turn to the alternative hypothesis Does the existence of psychological support according to the needs of the disabled patient , improve the quality of life of it? . We conclude that the labor market discriminates against disabled, given the limited information on this group was not possible to make a more comprehensive analysis . In recent years , significant advances have been achieved in terms of inclusion of people with disabilities into the labor market, thanks to the great support of institutions that have made significant legislative progress labor . Likewise that disability is an essential condition of the human being to be studied in greater depth because, through the manifestation of their extreme degrees , you can get to know its still unknown aspects of reality or have gone unnoticed until date. therefore let us recommend the following: Assist and support to people with disabilities, and their families, access to training , information and support services that enable them to live a fulfilling life. Evaluate and MCH services provided to adolescents, to ensure that children and youth are not disabled by services of poor health , malnutrition, poor hygiene, lack of immunization, family violence or lack of appropriate advice to parents; also assess occupational health services , to ensure that safety regulations are met , and also to evaluate health programs in the community, to ensure that appropriate health training for the prevention of accidents and diseases is taught . Educate the public so that people with disabilities can be integrated as much as possible in society